Potential of urban green spaces for supporting horticultural production: a national scale analysis - Walsh, Lael E.; Mead, Bethan R.; Hardman, Charlotte A.; Evans, Daniel L.; Liu, Lingxuan; Falagán, Natalia; Kourmpetli, Sofia; Davies, Jess (IOP Publishing, 2022)
As urban areas and land-use constraints grow, there is increasing interest in utilizing urban spaces for food production. Several studies have uncovered significant potential for urban growing to supplement production of fruit and vegetables, focusing on one or two cities as case studies, whilst others have assessed the global scale potential. Here, we provide a national-scale analysis of the horticultural production potential of urban green spaces, which is a relevant scale for agri-food and urban development policy making using Great Britain (GB) as a case study. Urban green spaces available for horticultural production across GB are identified and potential yields quantified based on three production options. The distribution of urban green spaces within 26 urban towns and cities across GB are then examined to understand the productive potential compared to their total extent and populations. Urban green spaces in GB, at their upper limit, have the capacity to support production that is 8× greater than current domestic production of fruit and vegetables. This amounts to 38% of current domestic production and imports combined, or >400% if exotic fruits and vegetables less suited to GB growing conditions are excluded. Most urban green spaces nationally are found to fall within a small number of categories, with private residential gardens and amenity spaces making up the majority of space. By examining towns and cities across GB in further detail, we find that the area of green space does not vary greatly between urban conurbations of different sizes, and all are found to have substantial potential to meet the dietary needs of the local urban population. This study highlights that national policies can be suitably developed to support urban agriculture and that making use of urban green spaces for food production could help to enhance the resilience of the national-scale food system to shocks in import pathways, or disruptions to domestic production and distribution.
Keywords: resilience; food sovereignty; urban agriculture; green spaces; horticultural production potential; towns and cities